A Methodology to Empirically Assess National and Farm-Specific Damages from Contamination of Grain Supply by a Genetically Engineered Strain. (August 2019) - Capps, Oral; Babula, Ronald A.
Abstract: On May 29, 2013, the U.S. government announced that contamination of non–genetically engineered wheat supplies occurred. We provide a methodology to empirically assess the impacts of this contamination event on national prices and on farm-specific prices and receipts for spring red hard wheat. Results suggest that U.S. spring red hard wheat farmers in the aggregate had lost receipts ranging from $32.77 million to $131.06 million and incurred a drop of 3.83% in wheat price equivalent to $0.27 per bushel. At the farm level, a hypothetical farmer received $0.31 less per bushel culminating in $4, 807 in lost receipts.